The supervision impact towards medical learning in experimentation evolution through the clinical knowledge and skills application - Saleh, Nor Shela; Yaacob, Hashim Fauzy (MCSER Publishing, 2015)
"This research conducted at Hospital Pakar Sultanah Fatimah, Johor. The purpose of this research is identifying the level of clinical skill and trainee doctor achievement in medical learning experimentation. Besides that, researcher will identify either the clinical supervision as a moderator or non-moderator. The data collected shown the researcher getting 98 of questionnaire returned. The researcher have been done do pilot study and the alpha cronbach finding is high. Next, the researcher analyse output through descriptive statistics (mean, frequency and percentage) and inferential statistic (pearson correlation and hierarchical regression. The output shown the level of clinical skills and knowledge used and the achievement of experimentation learning is high. The correlation analysis shown there are low positive correlation between clinical skills use with experimentation learning achievement. However, based on output the relationship is not influences by the supervision clinical moderator. The output shown the first hypothesis is accepted and second hypothesis was rejected"